The development of techniques for the identification of novel viruses associated with acute infantile gastroenteritis in South Africa - Jaquet, Brittany J (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2017)
Gastroenteritis is a serious disease affecting both children and adults globally, but is more predominant in children with over half a million deaths reported each year. The leading cause of this disease is rotavirus, which accounts for 38% of all hospitalised cases. There has, however, been a significant decrease in the number of deaths associated with rotavirus worldwide since the introduction of the two vaccines, Rotarix® and RotaTeq®. A large number of cases are therefore either associated with other viruses, such as norovirus, Aichi virus (AiV) or Saffold virus (SAFV), or are of unknown aetiology. This study thus aims to develop techniques for the identification of viruses associated with gastroenteritis. Theiler's murine encephalomyelitis virus (TMEV) was used to develop the sample preparation, transmission electron microscopy and RT-PCR techniques used in this study. This virus was chosen as a replication system using baby hamster kidney cells can be used to create high concentrations of viral particles from which RNA can be extracted preventing the waste of the limited samples. The virus particles are also similar in size and morphology to the viruses to be identified in this study, as it belongs to the same family. After sample preparation, TEM analysis showed the presence of small, round, non-enveloped virus particles in the TMEV sample. Due to the low concentration of virus particles, PEG precipitation was performed using both 0.15 M and 0.25 M NaCl and 8% (w/v) PEG 6000. TEM analysis then showed an increase in viral particle concentration, with the highest concentration observed at 0.25 M NaCl and 8% PEG 6000. RNA was successfully extracted and RT-PCR assays were performed for both the VP1 and 2B coding regions of TMEV. A method for creating a positive control for the RT-PCR assay was developed by the in vitro transcription of RNA from pTMEV, which contains the cDNA of TMEV. The RNA was then used as the template for the 2B two-step RT-PCR assay. A product of 412 bp was successfully amplified from the in vitro transcribed RNA and the sensitivity of the RT-PCR assay was determined. Using a Norovirus GII positive stool sample provided by Maureen Taylor, a nested RT-PCR assay was developed for the NoV GII N/S domain using a previously-published primer set and cycling parameters. A 342 bp product was successfully amplified from the RNA extracted from the stool sample and cloned into pGEM®-T Easy to produce pNoVGII. Using the plasmid containing the AiV 5'UTR and the PCR amplicon for AiV 3CD, RT-PCR assays were developed for AiV 5'UTR and partial 3CD. The RT-PCR assays produced a 1008 bp product for AiV 5'UTR and 266 bp for AiV 3CD, which were cloned into pGEM®-T Easy to produce pAiV5'UTR and pAiV3CD, respectively. Using in vitro transcribed RNA from pNoVGII, pAiV5'UTR, pAiV3CD and pSAFV, which contains the SAFV cDNA, positive controls were developed for the RT-PCR assays for NoV GII, AiV 5'UTR, AiV 3CD and SAFV 2C. The sensitivity of these assays was determined. The samples chosen for this study include wastewater collected from the Belmont Valley water treatment plant, oysters suspected to be infected with viruses collected from Port Elizabeth, South Africa and 30 stool samples from symptomatic patients. With the methods developed using TMEV, the wastewater, oysters and 30 stool samples were filter-sterilised, concentrated and screened by TEM. All samples showed the presence of virus particles. RNA was successfully extracted and the wastewater, oyster and 30 stool samples were screened for NoV GII using the NoV GII RT-PCR assay. The wastewater, oysters and 11 of the stool samples produced the 342 bp NoV GII PCR product and BLAST analysis determined the nucleotide sequences to be NoV GII.4. This shows that this study was able to develop sample preparation techniques and TEM analysis for selected samples and RT-PCR assays for NoV GII, AiV and SAFV. The NoV GII RT-PCR assay was successfully used for the screening of the wastewater, oysters and 30 stool samples for NoV GII. Due to the high number of gastroenteritis cases with unknown aetiology in South Africa, the development of techniques for the identification of NoV, AiV, SAFV and other viruses is very important. The identification of these viruses will allow for better surveillance, treatment and prevention of gastroenteritis in South Africa.
Keywords: Gastroenteritis in children -- Treatment; Gastroenteritis in children -- Treatment -- South Africa; Antiviral agents; Viral vaccines; Rotaviruses; Virus diseases in children